Activity Exerted by a Testosterone Derivative on Myocardial Injury Using an Ischemia/Reperfusion Model. (16th April 2014) - Lauro, Figueroa-Valverde; Francisco, Díaz-Cedillo; Elodia, García-Cervera; Eduardo, Pool-Gómez; Maria, López-Ramos; Marcela, Rosas-Nexticapa; Lenin, Hau-Heredia; Betty, Sarabia-Alcocer; Monica, Velázquez-Sarabia Betty
Abstract : Some reports indicate that several steroid derivatives have activity at cardiovascular level; nevertheless, there is scarce information about the activity exerted by the testosterone derivatives on cardiac injury caused by ischemia/reperfusion (I/R). Analyzing these data, in this study, a new testosterone derivative was synthetized with the objective of evaluating its effect on myocardial injury using an ischemia/reperfusion model. In addition, perfusion pressure and coronary resistance were evaluated in isolated rat hearts using the Langendorff technique. Additionally, molecular mechanism involved in the activity exerted by the testosterone derivative on perfusion pressure and coronary resistance was evaluated by measuring left ventricular pressure in the absence or presence of the following compounds: flutamide, prazosin, metoprolol, nifedipine, indomethacin, and PINANE TXA2 . The results showed that the testosterone derivative significantly increases P = 0.05 the perfusion pressure and coronary resistance in isolated heart. Other data indicate that the testosterone derivative increases left ventricular pressure in a dose-dependent manner (0.001–100 nM); however, this phenomenon was significantly inhibited P = 0.06 by indomethacin and PINANE-TXA2   P = 0.05 at a dose of 1 nM. In conclusion, these data suggest that testosterone derivative induces changes in the left ventricular pressure levels through thromboxane receptor activation.